Caffeine-Induced Suppression of GABAergic Inhibition and Calcium-Independent Metaplasticity - Masako Isokawa (Neural Plasticity)
GABAergic inhibition plays a critical role in the regulation of neuron excitability; thus, it is subject to modulations by many factors. Recent evidence suggests the elevation of intracellular calcium ([Ca2+]i) and calcium-dependent signaling molecules underlie the modulations. Caffeine induces a release of calcium from intracellular stores. We tested whether caffeine modulated GABAergic transmission by increasing [Ca2+]i. A brief local puff-application of caffeine to hippocampal CA1 pyramidal cells transiently suppressed GABAergic inhibitory postsynaptic currents (IPSCs) by 73.2 ± 6.98%. Time course of suppression and the subsequent recovery of IPSCs resembled DSI (depolarization-induced suppression of inhibition), mediated by endogenous cannabinoids that require a [Ca2+]i rise. However, unlike DSI, caffeine-induced suppression of IPSCs (CSI) persisted in the absence of a [Ca2+]i rise. Intracellular applications of BAPTA and ryanodine (which blocks caffeine-induced calcium release from intracellular stores) failed to prevent the generation of CSI. Surprisingly, ruthenium red, an inhibitor of multiple calcium permeable/release channels including those of stores, induced metaplasticity by amplifying the magnitude of CSI independently of calcium. This metaplasticity was accompanied with the generation of a large inward current. Although ionic basis of this inward current is undetermined, the present result demonstrates that caffeine has a robust Ca2+-independent inhibitory action on GABAergic inhibition and causes metaplasticity by opening plasma membrane channels.